Double gene targeting PCR assay for the detection of Crocodylus porosus in commercial products - Ahmad Nizar, Nina Naquiah; Ali, Md. Eaqub; Hossain, M.A. Motalib; Sultana, Sharmin; Ahamad, Mohammad Nasir Uddin (Taylor & Francis, 2018)
The demand for crocodile meat is quickly growing because of its exotic and organoleptic appeal and also the low content of cholesterol and lipids. Moreover, crocodile oil and blood have been used in alternative medicines for treating asthma and several other ailments since ancient times. Furthermore, crocodile hides have great demand in leather industries. All of these have collectively contributed to the extensive hunting, illegal trading and consequent decline of crocodiles in most parts of the world. To keep space with the growing demands, some crocodile species such as Crocodylus porosus have been raised in farms and its commercial trades have been legalised. However, demand for wild crocodiles in foods and medicines has continued in high gear. Recently, several DNA-based methods have been proposed for crocodile detection, but those assays are based on single gene and longer-sized amplicon targets that break down during extensive processing. To address this gap, here we developed and validated a highly stable double gene targeted multiplex PCR assay for the identification of C. porosus materials in commercial products. The assay involved two short sites from C. porosus atp6 (77 bp) and cytb (127 bp) genes and a universal internal control (99 bp) for eukaryotes. The PCR primers were cross-tested against 18 species and validated under pure and mixed matrices under extensive boiling, autoclaving and microwave cooking conditions. Finally, it was used to identify five crocodile-based commercial products. The lower limits of detection for atp6 and cytb genes were 0.001 ng and 0.01 ng DNA, respectively, in pure meat and 1% under mixed matrices. Some inherent features, such as 77–127 bp amplicon sizes, exceptional stability and superior sensitivity, suggested the assay could be used for the identification of C. porosus in any forensic specimen.